When Reflection Breaks Tradition: Gender Performativity in Disney’s Mulan (1998) - Jauwena, Gavriel Dylan; Kasenda, Clarisse Nicholtrayne; Gani, Shinelle Rose; Pranajaya, Nia; Siringoringo, Brigitta Esther Aprilya (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2025)
This study examines the construction and subversion of traditional gender roles in Disney’s Mulan (1998) through the lens of Judith Butler’s theory of gender performativity. Using a qualitative literary approach, the film was analyzed through close readings of key scenes, dialogues, and symbolic elements, supported by scholarly critiques and feminist theory. The findings reveal three main results. 1) the film reinforces traditional stereotypes by presenting femininity as obedience, domesticity, and marriage, particularly through the “Honor to Us All” sequence. 2) Mulan’s acts of disguise and performance destabilize the gender binary, illustrating Butler’s claim that gender is not innate but performed through repetition and cultural expectation. 3) while the narrative challenges conventional roles, it simultaneously reinscribes heteronormative closure by the film’s conclusion, reflecting Butler’s insight that performances of resistance can still be reabsorbed into existing norms. This study concludes that Mulan functions as both a critique and reinforcement of gender roles, highlighting the instability of gender identity and its potential for reinterpretation. The analysis contributes to broader feminist discussions on how literature and media negotiate cultural norms, offering new insights into the performative nature of gender in animated narratives.